Patterning embryos with oscillations: Structure, function and dynamics of the vertebrate segmentation clock - Oates, Andrew C. (2012)
The segmentation clock is an oscillating genetic network thought to govern the rhythmic and sequential subdivision of the elongating body axis of the vertebrate embryo into somites: the precursors of the segmented vertebral column. Understanding how the rhythmic signal arises, how it achieves precision and how it patterns the embryo remain challenging issues. Recent work has provided evidence of how the period of the segmentation clock is regulated and how this affects the anatomy of the embryo. The ongoing development of realtime clock reporters and mathematical models promise novel insight into the dynamic behavior of the clock. © 2012. Published by The Company of Biologists Ltd.